2020
DOI: 10.3390/nano10091782
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Photo-Excitation on Leakage Current and Negative Bias Instability in InSnZnO Thickness-Varied Thin-Film Transistors

Abstract: InSnZnO thin-film transistors (ITZO TFTs), having high carrier mobility, guarantee the benefits of potential applications in the next generation of super-high-definition flat-panel displays. However, the impact of photo-excitation on the leakage current and negative bias stress (NBIS) of ITZO TFTs must be further explored. In this study, the ITZO thickness (TITZO) is designed to tailor the initial performance of devices, especially for the 100 nm TITZO TFT, producing excellent electrical properties of 44.26 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The oxygen-related species present in oxide thin-film transistors (TFTs), such as oxygen vacancies (V O ) or hydroxyl (OH) groups, have a significant impact on the stability and electrical characteristics of the TFTs [9,10]. Thus far, extensive studies have been conducted to investigate the effects of various process conditions on the concentration of oxygen-related species in the oxide channel layer [11][12][13][14][15][16][17]. The post-deposition annealing atmosphere has a particularly strong influence on the number of oxygen species within the channel layer and also affects the electrical properties and stability of oxide TFTs with various channel materials [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen-related species present in oxide thin-film transistors (TFTs), such as oxygen vacancies (V O ) or hydroxyl (OH) groups, have a significant impact on the stability and electrical characteristics of the TFTs [9,10]. Thus far, extensive studies have been conducted to investigate the effects of various process conditions on the concentration of oxygen-related species in the oxide channel layer [11][12][13][14][15][16][17]. The post-deposition annealing atmosphere has a particularly strong influence on the number of oxygen species within the channel layer and also affects the electrical properties and stability of oxide TFTs with various channel materials [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[3] This increase depends on the photon energy of incident light. [4] In this technology, TFT devices are covered by color resistance. Therefore, the TFT device is less affected by light and has a longer lifespan.…”
Section: Lcd Panel Experiments and Design 21 Panel Designmentioning
confidence: 99%
“…However, this high mobility and stability is still not sufficient for next generation displays which require fe of the order of 20. Wang et al [20] proposed a-ITZO as an alternative of IGZO with high fe (~ 44) and good stability. Zhong et al [21] reported that ITZO is a potential TFT channel material as it offers high mobility of 19 cm 2 V −1 s −1 , and subthreshold swing of 0.6 V. Based upon the past literature, it can be concluded that a-ITZO has all potential properties that makes it a potential material for TFTs.…”
Section: Introductionmentioning
confidence: 99%